Español Identification and Analysis of Metacognitive Strategies for Reading Comprehension among High School Students (Revista Electrónica Calidad en la Educación Superior, 2025)
This article presents an analysis of the metacognitive reading strategies implemented by a group of tenth-grade Costa Rican students before, during, and after reading a text. To achieve this, a qualitative methodology with a three-stage design was proposed, as well as an instrument developed by the researcher to collect information. The results indicate that the participating students use strategies such as predicting based on paratexts, questioning themselves, or summarizing. However, the study concludes that they do not fully apply strategies that would allow them, on the one hand, to self-regulate their reading process and, on the other, to embark on a path of improvement in their development as readers.
Keywords: reading; reading habit; reading instruction; reading strategies; metacognition